PSVII-5 Effects of Hops Treatment on Nitrogen Retention of Composted Poultry Litter and Subsequent Rumen Fermentation. (21st September 2022) - Castillo-Castillo, Yamicela; Anderson, Robin C; Hume, Michael E; Nisbet, David J; Flythe, Michael; Arzola-Alvarez, Claudio; Angulo-Montoya, Claudio; Salinas-Chavira, Jaime; Castillo-Rangel, Francisco; Felix-Portillo, Monserrath; Ontiveros-Magadan, Marina; Ruiz-Barrera, Oscar
Abstract: We tested the effects of Galena or Chinook hops treatment (6% wt/wt) of simulated composts (13 d) of wood chip litter (WCL) alone or mixed 3:1 with ground Bluestem hay (BSH). Results revealed that net losses of urea and ammonia in the WCL litter composted without BSH (n = 3/treatment) were unaffected by hops treatment (P = 0.37 and 0.13, respectively), averaging 0.32 ± 0.7 and 0.03 ± 1.5 µmol/g, respectively). The loss of uric acid was 60% less (P = 0.04) in the Galena hops-treated WCL compost than in the negative control compost (13.9 ± 3.8 vs 24.4 ± 5.6 µmol/g, respectively) and intermediate in the Chinook-treated compost (16.0 ± 2.7 µmol/g). Nitrogen losses during compost of WCL: BSH (n = 2/treatment) were unaffected by hops treatment (P = 0.77, 0.73 and 0.14 for uric acid, urea and ammonia, respectively), averaging 12.21 ± 3.1, 0.64 ± 0.6 and 1.07 ± 0.1 µmol/g, respectively, respectively). Assessment of potential carry over effects of residual hops in the composts during in vitro rumen fermentation (0.2 g of treated and control compost, in triplicate, mixed with 10 mL freshly collected rumen fluid) for 24 h at 39 o C under 100% CO2 revealed no effects of hops treatment on H2 accumulations in incubations with WCL or WCL: BSH composts (P = 0.22 and 0.17, respectively), averaging 0.23 ± 0.1 and 0.17 ± 0.1 µmol/mL fluid, respectively. Accumulations of CH4 in rumen incubations of WCL composts were unaffected by hops treatment (P = 0.24), averaging 15.07 ± 2.0 µmol/mL, but were increased (P = 0.0002) in incubations of WCL: BSH composts, averaging 14.1 ± 0.4 and 13. 8 ± 0.6 µmol/mL in Galena- and Chinook-treated compost compared with 11.2 ± 0.4 µmol/mL in control incubations. Results indicate hops treatment may lessen uric acid degradation composting poultry litter without inhibiting rumen fermentation.